2011
DOI: 10.1016/j.nbd.2010.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Adult neurogenesis and neurite outgrowth are impaired in LRRK2 G2019S mice

Abstract: The generation and maturation of adult neural stem/progenitor cells are impaired in many neurodegenerative diseases, among them Parkinson’s disease (PD). In mammals, including humans, adult neurogenesis is a lifelong feature of cellular brain plasticity in the hippocampal dentate gyrus (DG) and in the subventricular zone (SVZ)/olfactory bulb system. Hyposmia, depression, and anxiety are early non-motor symptoms in PD. There are parallels between brain regions associated with non-motor symptoms in PD and neurog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(173 citation statements)
references
References 65 publications
7
162
3
1
Order By: Relevance
“…As reported by other investigators in different cell types [53][54][55][56][57][58][59], we also observed that the overexpression of LRRK2 G2019S results in shortened neuritic extensions. We explored potential molecular contributors to this pathogenic neuritic phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…As reported by other investigators in different cell types [53][54][55][56][57][58][59], we also observed that the overexpression of LRRK2 G2019S results in shortened neuritic extensions. We explored potential molecular contributors to this pathogenic neuritic phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, LRRK2 is expressed in NSCs isolated from both the DG and SVZ of E18.5 mice. The LRRK2 protein may interact with the regulator of neurite outgrowth during embryonic neurogenesis, CRMP2 [77] and numerous studies have demonstrated that mutant LRRK2 overexpression decreases neurite length/outgrowth, while LRRK2 deficits result in an increase of neurite length and arborization [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94]. Moreover, LRRK2 has been shown to bind Wnt signaling components (the DVL proteins) and play a role in the canonical Wnt/bcatenin signaling pathway, an important pathway for neurogenesis and in particular the development of DA neurons [83,95,96].…”
Section: Evidence For a Developmental Component Of Pd: Deregulated Emmentioning
confidence: 99%
“…Indeed, transgenic mice overexpressing the PD-associated human LRRK2 G2019S protein display a significant decrease in the number of proliferating (BrdU positive) cells in the adult DG, SVZ and RMS and decreased neurogenesis (BrdU and NeuN positive) and DA neurogenesis (BrdU, NeuN and TH positive) as well as decreased survival of newly generated neurons in the OB [86]. The LRRK2 G2019S mutation may contribute to the hippocampal and SVZ-related age-dependent non-motor symptoms via dysfunctions in the NSC pool and in their neural derivatives at early stages of maturation.…”
Section: Overexpression Of Mutated Lrrk2mentioning
confidence: 99%
“…This strategy could be useful in scenarios where proliferation itself has been reduced by the particular disease, like Parkinson disease. [84][85][86][87] In many diseases and injury, maturation and/or survival are also impaired. For differentiation, Ca v 1 voltage-gated Ca 2+ channels as well as other yet to be identified channels involved in maturation could be stimulated (e.g., Bay K8644) to enhance differentiation.…”
Section: Summary-targeting Specific Channels For Brain Repairmentioning
confidence: 99%